2005
DOI: 10.1111/j.1551-2916.2005.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Patterned Inorganic–Organic Hybrid Film for the Optical Waveguide by Microfluidic Lithography

Abstract: Inorganic–organic hybrid materials for the optical waveguide were synthesized by the sol–gel process starting from the acid‐catalyzed solutions of phenyltrimethoxysilane, methyltriethoxysilane, and tetraethylorthosilicate. The control of the refractive index in the organically modified silicate films was achieved by varying the content of phenyltrimethoxysilane incorporated as a refractive index modifier. A single spin‐coating with the precursor solution produced a crack‐free buffer layer of 22‐μm thickness wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Put another way, the glass transition is associated with a temperature T g , which is influenced by a number of macroscopic properties, such as viscosity, dielectric constant, and mechanical properties. Using the approach developed for traditional organic polymers and applied to inorganic silica-based polymers [22], the glass transition temperature is considered a measure of the degree of cross-linking in the silica network. In other words, the T g increases with an increase in the number of oxygen bridges between silicon atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Put another way, the glass transition is associated with a temperature T g , which is influenced by a number of macroscopic properties, such as viscosity, dielectric constant, and mechanical properties. Using the approach developed for traditional organic polymers and applied to inorganic silica-based polymers [22], the glass transition temperature is considered a measure of the degree of cross-linking in the silica network. In other words, the T g increases with an increase in the number of oxygen bridges between silicon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Since the refractive index and the thickness of hybrid coatings can be adjusted, waveguides based on phenyltriethoxysilane (PhTES), MTES and TEOS have been patterned by microfluidic lithography [22,23]. Using a mixture of TEOS, MTES and DMDES, a planar integrated waveguide for water vapor sensing, was obtained by doping with Erytrosin B [24].…”
Section: Background Of ''Ormosils''mentioning
confidence: 99%
“…Moreover, optical properties like transmittance and refractive index can be controlled through proper selection of the organic groups, which is why these materials are so popular for these applications. 89 A comparison between soft lithographically produced photonic crystal laser resonators from epoxideand methyl-functional organosilanes, and photolithographically fabricated resonators in silicon showed that the laser emission spectra were of equal quality. 90 Patterned features were ∼500 nm in width and ∼50 nm in depth, and could be solidified at 60 • C.…”
Section: Glasses and Hybrids For Optics And Dielectricsmentioning
confidence: 98%
“…A simpler alternative to increase the rate of infiltration was proposed by Jeong, Ahn, and Moon, 89 who filled macroscopic reservoirs in direct contact with the microchannel system with a sol-gel silsesquioxane-based precursor solution. After evacuating the entire chamber to 10 Torr and then returning to atmospheric pressure, the microchannels filled within seconds.…”
Section: Micromoulding In Capillaries (Mimic)mentioning
confidence: 99%
See 1 more Smart Citation